Sintesis penyangga katalis gamma alumina dari aluminium sulfat - Lintang Adi Pradana; Kemal Naser; T Walmiki Samadhi; IGBN Makertihartha (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2008)
Hydrotreating is a processing step in petroleum refinery, whose purpose is to remove impurities in refining feedstock. The performance of a hydrotreater is determined by the catalyst used in the process. One of the commonly used materials for catalyst support is gamma alumina, which in Indonesia is still being imported. The objective of this research is to define the recipe (operating conditions and working procedures) for synthesizing commercial-quality gamma alumina powder, as indicated by crystal structure and specific surface area specifications. The synthesis method used in this research is based on the procedure patented by Rana (2004). Gamma alumina is synthesized via precipitation, using technical grade alum (aluminum sulfate) as alumina source, and urea, ammonium hydroxide, and ammonium carbonate as precipitating agents. Alumina hydrate calcination temperature is varied at 550, 650 and 750°C. Calcination time is varied at 5 and 10 hours. Optimum calcination condition is achieved at a temperature of 750 °C for 10 hours. From the main experiment, it has been identified that gamma alumina with the best crystal structure is obtained by using ammonium carbonate as precipitating agent. The highest specific surface area is obtained by using continuous heating and stirring, using urea precipitating agent.Keywords: hydrotreating, gamma alumina, precipitation AbstrakHydrotreating merupakan tahapan pengolahan minyak bumi untuk menghilangkan pengotor di dalamnya. Kinerjanya dipengaruhi oleh katalis yang digunakan. Salah satu komponen katalis adalah penyangga. Bahan yang umum digunakan sebagai penyangga katalis hydrotreating adalah gamma alumina. Gamma alumina yang digunakan di Indonesia masih diimpor. Tujuan penelitian adalah menentukan resep (kondisi operasi dan prosedur kerja) sintesis gamma alumina fasa serbuk dengan kualitas komersial, yang mencakup spesifikasi struktur kristal dan luas permukaan. Sintesis gamma alumina pada penelitian ini menggunakan prosedur yang dipatenkan oleh Rana). Metode yang dilakukan adalah presipitasi dengan bahan baku tawas dan presipitator berupa urea, amonium hidroksida, dan amonium karbonat. Temperatur kalsinasi divariasikan pada 550, 650, dan 750°C. Waktu kalsinasi divariasikan pada 5 dan 10 jam. Kondisi optimum dicapai pada temperature kalsinasi 750°C selama 10 jam. Dari percobaan inti didapatkan bahwa gamma alumina dengan struktur kristal terbaik diperoleh dari presipitator amonium karbonat. Gamma alumina dengan luas permukaan terbesar diperoleh dari metode pemanasan serta pengadukan kontinu menggunakan presipitator urea.Kata kunci: hydrotreating, gamma alumina, presipitasi